KAJIAN SINGKAT MORFOLOGIS ISTILAH-ISTILAH AGAMA HINDU DI BALI - I MADE SUWETA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Speaking of Bali as one of the languages of culture, of course, is closely related to religion. People in Bali majority embraced Hinduism. There are many terms or vocabulary in Hinduism. The terms contained in the Hindu religion in society will be a lot of additive or affixation in the pronunciation and also will have a different meaning. Based on the background that has been described in the datas, the issues raised in this study was formulated in the form of questions as follows: (1) How do the basic words of Balinese language in terms of Hinduism? and (2) How the Bali language morphological system in terms of Hinduism?. The method in this study include methods of data collection by the literature, which is done by reading a variety of resources related to the terms of Hinduism that includes basic words, invented words, repeated words, and compound words. Furthermore, the data that has been analyzed by descriptive synchronic, ie, the analysis done by describing the data found with the words in a narrative. Based on this analysis obtained results of the study as follows. There are terms in Hinduism that can be assessed based on the study of morphological, includes basic words (not received prefixes), derivatives (get the process of affixation, either by adding a prefix, infix, suffix, and konfiks), said repeated (repetition), and compound word (a combination of two or more words that generate new meanings).